"Dr. Werthless" - Schechter, Harold; Powell, Eric (Dark Horse Books, a division of Dark Horse Comics, 2025)
"Reviled by comic book fans as a witch-hunting zealot who stirred up a panic among the parents of America for his own self-promoting purposes, he was also a renowned psychiatrists who, among other accomplishments, opened a clinic in Harlem for disadvantaged African-American patients and played an important role in the desegregation of the nation's schools. Believing that murder could be abolished through a proper understanding of the mental and social roots of criminal violence, he took a genuinely humane approach to some of the most notorious homicidal maniacs of his time, while simultaneously exploiting their stories for his own commercial ends. Acclaimed true crime author, Harold Schechter, and multiple Eisner award winning cartoonist, Eric Powell, present a graphic novel that takes an unbiased look at this flawed and enormously and complex man--whose obsessive dream of freeing the world from violence nearly murdered the comics industry." --